Randomized controlled trials in pediatric complementary and alternative medicine: Where can they be found? - Ajiferuke Isola; Campbell Kaitryn; Sampson Margaret; Moher David (BMC, 2003)
Abstract Background The safety and effectiveness of CAM interventions are of great relevance to pediatric health care providers. The objective of this study is to identify sources of reported randomized controlled trials (RCTs) in the field of pediatric complementary and alternative medicine (CAM). Methods Reports of RCTs were identified by searching Medline and 12 additional bibliographic databases and by reviewing the reference lists of previously identified pediatric CAM systematic reviews. Results We identified 908 reports of RCTs that included children under 18 and investigated a CAM therapy. Since 1965, there has been a steady growth in the number of these trials that are being published. The four journals that published the most reported RCTs are The American Journal of Clinical Nutrition, Pediatrics, Journal of Pediatrics, and Lancet. Medline, CAB Health, and Embase were the best database sources for identifying these studies; they indexed 93.2%, 58.4% and 42.2 % respectively of the journals publishing reports of pediatric CAM RCTs. Conclusions Those working or interested in the field of pediatric CAM should routinely search Medline, CAB Health and Embase for literature in the field. The four core journals identified above should be included in their collection.